A pesquisa de um trabalho colaborativo com docentes de matemática envolvendo textos: uma proposta de formação continuada - Susana Lúcia do Nascimento (2023)
The present work has the general objective of explaining and analyzing a proposal for Continuing Education based on Collaborative Work in the development of a planning of activities using mathematical and non-mathematical texts. Three Mathematics teachers who work in the final years of Elementary Education in Public Schools in the city of Ponte Nova, Minas Gerais, participated in this research as collaborators. This research, of a qualitative nature, brings as a methodological proposal the formation of a Collaborative Work Group in the development of theoretical studies, planning of teaching activities and reflections on practice. In the end, we will present an educational resource with the activities discussed and defined by the group with the objective of presenting a support material for teachers in the final years of Elementary School. The product will be organized in an e-book format, considered important due to its efficiency from a pedagogical point of view, as it complements and provides opportunities for new didactic approaches, as it guides on a collaborative action, in our case, the use of mathematical and non-mathematical texts. mathematicians in mathematics teaching.